English Language Learning Strategies Integrated with Technology to Improve the Learning Outcomes of Junior High School Students in Palu City - Rengur, Zul Aini; Kumala, Shofa Aulia; Fajrin, Maghfiroh (Yayasan Pendidikan Bima Berilmu, 2024)
This study investigates how English language learning strategies integrated with technology impact the learning outcomes of junior high school students in Palu City. The research employs a mixed-methods approach, combining quantitative surveys, pre- and post-tests, qualitative interviews with teachers, and classroom observations. A total of 150 students from three schools participated, providing data on their perceptions of technology in learning English and their proficiency in reading, writing, speaking, and listening skills. Quantitative analysis revealed significant improvements in all tested skills following the implementation of technology-integrated strategies, supported by statistical findings (p < 0.05). Surveys indicated positive student attitudes towards technology, citing increased understanding, motivation, and enjoyment in learning English. However, challenges such as limited digital access outside school hours were identified. Qualitative insights from teacher interviews highlighted benefits like enhanced student engagement but also underscored the need for ongoing professional development and equitable access to digital resources. Classroom observations illustrated varied implementation and student engagement levels, emphasizing the importance of pedagogical alignment and effective use of technology in language teaching. This study contributes to the discourse on technology-enhanced education in diverse contexts, offering practical recommendations for improving English language learning outcomes in Palu City's junior high schools.